(untitled) (Global Journal of Science Frontier Research, 2015)
We have studied the Hoyle-Narlikar’s Creation-field cosmology for LRS Bianchi type-II, LRS Bianchi type-VI 0 , Plane Symmetric and Kantowski-Sachs universes with time dependent cosmological constant ) (t Λ , when the universe is filled with dust distribution. To get deterministic model of the universe, a relation between shear ) (σ and expansion ) (θ is assumed. The physical aspects of the models are also discussed.